La Estabilidad Emocional Del Nucleo Familiar Y Su Incidencia En Los Aprendizajes Significativos De Los Estudiantes De La Unidad Educativa Replica “Eugenio Espejo” De La Ciudad De Babahoyo. - Rivadeneira Coello, Irene (2015)
This research study is enmaracado in the family and focuses on researching emotional stability and as a result is given as the academic performance of young replica of the Education Unit "Eugenio Espejo" Babahoyo City. The issue comes to research focusing on the family jcleo having the same importance and relevance in the topic to study. Data confirming agree even detailed study of the pedagogical work, emotions and family are delivered. Theoretical and empirical antecedents that support this research are discussed. Didactic and emotions of young pedagogical texts are reviewed. In this investigation a series of concepts and theories that led to the analysis of data frames. With erspecto methodology and survey techniques were used, once the data collected is carried out a content analysis, which subsequently allowed the construction of an action plan. After the analysis and interpretation of the results obtained in the investigation, they are considered the conclusions and reflections about the contents covered in the investigation, and allowing open a new space to discuss the issue relevant events giving rise to further research with new questions raised by research in the process. Finally framed what to improve family communication and family atmosphere and thus academic performance activities proposed. That's why during the investigation process was noted that emotions are tied very closely with academic performance. With these considerations the contribution of the family to children and youth. Finally a proposal for improving the academic performance of emotional stability withthe young projecting to further unite the family and recognizing them as the core to balance their emotions is established. In closing I share the following sentence "The only rock that remains constant, the only institution that works is the family." (Lee Iacocca).